2019
DOI: 10.2478/msp-2019-0081
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and thermal characteristics of MWCNTs modified carbon fiber/epoxy composite films

Abstract: To enhance interfacial bonding between carbon fibers and epoxy matrix, the carbon fibers have been modified with multiwall carbon nanotubes (MWCNTs) using the dip-coating technique. FT-IR spectrum of the MWCNTs shows a peak at 1640 cm −1 corresponding to the stretching mode of the C=C double bond which forms the framework of the carbon nanotube sidewall. The broad peak at 3430 cm −1 is due to O-H stretching vibration of hydroxyl groups and the peak at 1712 cm −1 corresponds to the carboxylic (C=O) group attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Polymer electrolytes were commonly researched. Unfortunately, those polymer electrolyte types have exhibited low electrode-electrolyte contact or insufficient mechanical stability, thus, were deprived of the general efficiency [7]. In order to improve ionic conductivity of the PVA film, sulfuric acid was used as sulfonating as well as cross-linking agent [8].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer electrolytes were commonly researched. Unfortunately, those polymer electrolyte types have exhibited low electrode-electrolyte contact or insufficient mechanical stability, thus, were deprived of the general efficiency [7]. In order to improve ionic conductivity of the PVA film, sulfuric acid was used as sulfonating as well as cross-linking agent [8].…”
Section: Introductionmentioning
confidence: 99%
“…The MSD curves of C‐PE in C‐PE/CNT system are slightly lower than that of pure C‐PE, because the adsorption force of the CNT on C‐PE affects the mobility of chain segments to a certain extent 26 . Similarly, it has been reported that the presence of strong interactions in MWCNTs modified carbon fiber/epoxy composite (MWCNTs‐CF/Ep) can restrict molecular motion in the experiment 47 . The MSD values of C‐PE in the CNT‐ g ‐PE system are significantly less than that of the other two systems.…”
Section: Resultsmentioning
confidence: 96%
“…26 Similarly, it has been reported that the presence of strong interactions in MWCNTs modified carbon fiber/epoxy composite (MWCNTs-CF/Ep) can restrict molecular motion in the experiment. 47 The MSD values of C-PE in the CNT-g-PE system are significantly less than that of the other two systems. This result indicates that the addition of the CNT-g-PE considerably reduced the movement capability of the C-PE chains.…”
Section: Isothermal Crystallization Process Of C-pe C-pe/cnt and C-pe...mentioning
confidence: 87%
“…They not only possess outstanding processability but also exhibit excellent adhesiveness and weather resistance. [7][8][9][10] In addition, the coating process is environmentally friendly and chemically stable with low volatility. 11,12 Furthermore, the addition of intrinsically conducting polymer (ICP) nanofillers, such as polyimide, polypyrrole, polythiophene, and polyaniline (PANI), to epoxy coatings can remarkably improve the anticorrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among the available anticorrosive techniques, epoxy coating systems are the most common type of protective coating. They not only possess outstanding processability but also exhibit excellent adhesiveness and weather resistance 7–10 . In addition, the coating process is environmentally friendly and chemically stable with low volatility 11,12 .…”
Section: Introductionmentioning
confidence: 99%